An Investigation and Simulation of Frequency Controlled Electric Drive System - Kriauciunas, J.; Rinkeviciene, R. (Elektronika ir Elektrotechnika, 2013)
Paper presents experimental and simulation results with 4 kW induction motor drive. Experiments are done using hardware in the loop real time simulation which allows implementing of motor control directly from the personal computer. This technique enables to replace part of the system with computer model running software. Regulator model was simulated in Matlab/Simulink. PI and PID regulators were tested. Experimental and simulation results starting and loading the motor are elaborated. DOI: http://dx.doi.org/10.5755/j01.eee.19.2.3463